Self-organization of TiO2 nanotubes in mono-, di- and tri-ethylene glycol electrolytes. (20th June 2016) - Kowalski, Damian; Mallet, Jeremy; Thomas, Shibin; Rysz, Jakub; Bercu, Bogdan; Michel, Jean; Molinari, Michael
Graphical abstract: Anodizing of titanium in electrolytes containing 1, 2, and 3 oxyethylene units in the organic chain of solvent molecule named mono-, di-, and tri-ethylene glycols leads to formation of TiO2 with distinctive porous structures. Highlights: Anodizing of titanium in electrolytes containing 1, 2, and 3 oxyethylene units in the organic chain of solvent molecule. Self-organization of nanotubes by means of control of interconnecting space in between nanotubes. Formation of and frustrum-type dimples in di-ethylene glycol electrolyte. Abstract: Self-organization of TiO2 nanotubes was studied by means of titanium anodizing in electrolytes containing 1, 2 and 3 oxyethylene units in the organic chain of solvent molecule, named mono-, di-, and tri-ethylene glycols. A fundamentally different nanostructures were formed in mono- and di-electrolytes in view of their self-organization; close pack nanotubes are formed in mono-electrolyte, whereas nanotubes with large spaceing in-between are formed in di-electrolyte. The analysis of the tube bottoms and dimples formed in substrate shows formation of conical-type (alumina like) and frustum-type dimples in mono- and di-electrolytes, respectively. We discuss on the formation of frustum-type dimples with the size corresponding to the space in-between the nanotubes and link their formation to the mechanism of nanostructure growth.